Implementation of the Social Sciences Learning Model with the Jigsaw Approach to the Ability of Class X Students at SMK Negeri 3 Manado - Rieneke R. Kalalo; Jola Silvana Kalangi; Welky Karauwan; Yopie AT Pangemanan; Matiti Kalempouw (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
Efforts to improve student achievement can be started by procuring various factors influencing it. One crucial factor is to present a variety of teacher-teaching methods. Teachers very much need these factors and are more creative in carrying out more interesting learning so that students like the teacher and the content taught. Applying a Jigsaw approach or cooperative learning for students so that they have significant responsibility in learning can inspire students to speak in front of the class. This study aims to determine students' understanding of social studies through learning with the Jigsaw method of choice in class X SMK Negeri 3 Manado. With a qualitative design and a descriptive approach strategy, this study is expected to understand the level of mastery of social studies content using the Jigsaw method and approach. Data collection techniques are data analysis from a series of teacher interviews and direct observations in the classroom. A single case study because it only chose one location. The case study is anchored because it has focused on the problem under study before researching the field. The procedure for implementing qualitative research is flexible according to the field's needs, situations, and conditions. In general, the results of qualitative research show that it is closely related to achieving effective and efficient learning objectives. The relationship between the material and the tasks carried out by students needs to be clarified so that each group and its members need clarification about the discussion material and its objectives. In this connection, it is unwise for teachers to criticize students' opinions, especially their criticisms, constantly. Keywords:  Jigsaw Approach, Social Sciences, Learning Model